Are zoonotic Staphylococcus pseudintermedius strains a growing threat for humans? - Kmieciak, Wioletta; Szewczyk, Eligia Maria (Folia microbiologica, 2018)
Staphylococcus pseudintermedius is a species often isolated from animals, as a common element of their microbiota or an agent of infection, and from people associated with an animal habitat, including owners of home pets-dogs and cats. As with many other species, adaptation of these bacteria to the human body can occur, and they become important human pathogens. 59 S. pseudintermedius strains were investigated in this study to determine the factors contributing to human body colonization: inhibition growth of human skin residents isolated from human skin (Staphylococcus epidermidis, Corynebacterium spp., Cutibacterium acnes (formerly Propionibacterium acnes)), biofilm formation, and the presence of ten genes encoding infection-promoting features (including ebpS, spsE, lukS, lukF, pvl, lip, hlgA, hlgB). The ability of human skin to be colonized and the presence of genes that promote the development of skin infections showed the significant potential of the studied strains in their adaptation to the host. However, while a comparison of the characteristics of animal strains and those isolated from human infections does not allow us to claim that we are the witnesses of the speciation of a new human pathogen, it does indicate their gradual adaptation to the human organism.
Keywords: Staphylococcus; Animals; Dogs; Genes, Bacterial; virulence; Staphylococcal Infections; stafylokokové infekce; Cats; Zoonoses; Staphylococcus pseudintermedius; bakteriální geny; Humans; Phenotype; kočky; lidé; fenotyp; psi; Companion animals; zvířata; mikrobiota; Skin microflora; Microbiota; Colonization; Virulence; zoonózy